CHARACTER CONSTRUCTION OF SONGS IN KIDUNG JEMAAT: A TRANSITIVITY ANALYSIS - Tresha Elyenta Rumapea; Desminar Debora Rangkuti; Arsen Nahum Pasaribu (Jurnal Education and Development, 2022)
The focus of this study is to find the character construction that found in Kidung Jemaat songs No. 316-318 about marriage. This study is descriptive quantitative. The data in this study were taken from the lyrics of the Kidung Jemaat songs. M.A.K Halliday’ Systemic Functional Grammar is the tool to analyze this study. The use of language in the song lyrics in Kidung Jemaat has the aim of producing actions based on the meaning of the song. It means not just to sing, but to do. As the result of data analysis, the process types used in Kidung Jemaat songs no. 316-318 are material process 64,7%, mental process 17,6%, relational process 11,8%, and behavioral process 5,9%. the material process that appears the most, which means that the character construction that is built is to persuade and commemorate the congregation who is getting married to build their household in Jesus Christ.